2020
DOI: 10.29333/ejgm/7904
|View full text |Cite
|
Sign up to set email alerts
|

Application of New TOPSIS Approach to Identify the Most Significant Risk Factor and Continuous Monitoring of Death of COVID-19

Abstract: A pandemic is a disease that spreads across a large area like multiple continents or worldwide. More than 211 nations are already affected by Covid-19. The World Health Organization (WHO) on 11 March 2020 declared Covid-19 a pandemic. There are more than 1,282,931 cases of the coronavirus illness over 211 countries and territories around the world. Currently coronavirus has no proper treatment in Medical Science, increasing the number of affected people day by day with the number of cases worldwide of novel co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
31
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(37 citation statements)
references
References 22 publications
0
31
0
Order By: Relevance
“…This framework can assist decision-makers in medical organisations to determine the optimal classifier for COVID-19 diagnosis. Another work [ 32 ] presented a real-time death assessment monitoring of COVID-19 using TOPSIS MCDM to select most important risk factors and applied GMDH to estimate death value within all confirmed cases. A study [ 33 ] investigated some elected activities and evaluated their importance and suggested that many activities should not be performed during the COVID 19 pandemic period.…”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…This framework can assist decision-makers in medical organisations to determine the optimal classifier for COVID-19 diagnosis. Another work [ 32 ] presented a real-time death assessment monitoring of COVID-19 using TOPSIS MCDM to select most important risk factors and applied GMDH to estimate death value within all confirmed cases. A study [ 33 ] investigated some elected activities and evaluated their importance and suggested that many activities should not be performed during the COVID 19 pandemic period.…”
Section: Literature Reviewmentioning
confidence: 99%
“… Aim of the study Method used Criteria used Case study [ 31 ] Evaluation and benchmarking methodology to select the best classifiers for COVID-19 diagnosis Entropy–TOPSIS Main criteria: time-complexity group reliability, reliability Sub-criteria: precision, f1-score, recall, average accuracy, error rate, TP, TN, FP, FN Public data sources from hospitals and physicians of chest X-ray and CT images for positive or suspected patients of COVID-19, MERS, SARS, and ARDS. [ 32 ] Characterise the most important risk factors of corona virus Real-time monitoring of pandemic prevalence TOPSIS GMDH (Group Method of Data Handling) Important risk factors of COVID-19 Confirmed and death cases collected from website of (WHO) and some Government report between 31-Dec-2019 to 05-Apr-2020. [ 33 ] Remedial activity prioritisation AHP Social distancing, Hygiene, Shared individual things, Needless of touch-things, items of daily fresh food, and Immunity/fitness Guidelines and safety measures from WHO and governing organisations of diverse countries [ 34 ] COVID-19 patient prioritisation dependent on their health conditions AHP and VIKOR laboratory examinations (CRP, eosinophil ratios, eosinophils, white blood cell count, lymphocyte ratios, lymphocytes, neutrophil ratios, neutrophils) Six patients with COVID-19 (included 1 Asymptomatic Carrier with COVID-19) The presented Study Prioritisation and detection of asymptomatic carriers with COVID-19 Two feature selection approaches: automatic mechanisms (ANOVA, ) and knowledge-driven (expert judgment) ENTROPY–TOPSIS (MCDM) Objective validation Multi-laboratory Characteristics (White blood cell count, count of Neutrophil, count of Lymphocyte, Haemoglobin, count of Blood pla...…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…On March 11, 2020, the WHO declared the COVID-19 as a pandemic. There is no proper treatment for the COVID-19 in Medical Science and the number of people affected is increasing every day (Majumder et al 2020). As of September 6, 2020, over 26 million people worldwide were infected with SARS-CoV-2 virus, and nearly 900 thousand people have died because of the COVID-19.…”
Section: The Covid-19 and Development Processmentioning
confidence: 99%
“…Individuals should prevent the spread of the virus by constantly washing their hands again, using personal protective equipment (masks) to protect their health. Thus, they should reduce risk factors (Majumder et al 2020).…”
Section: The Covid-19 and Development Processmentioning
confidence: 99%